Association between metabolic syndrome and its components and incident colorectal cancer in a prospective cohort study. Issue 6 (11th November 2021) - Tran, Tao Thi; Gunathilake, Madhawa; Lee, Jeonghee; Kim, Jeongseon
Abstract : Background: Metabolic syndrome (MetS) has been identified as a contributor to cancer development. However, reports concerning the association between MetS and colorectal cancer (CRC) have been inconsistent. This study investigated whether MetS, its components, and the number of components increase the risk of CRC. Methods: This was a prospective cohort study of 41, 837 participants recruited from August 2002 to December 2014 from the National Cancer Center in South Korea. The participants were followed until December 2017 to identify incident CRC cases. The participants underwent laboratory tests at the baseline. Additionally, a self‐administered questionnaire collected information concerning lifestyle and general characteristics at the baseline. A Cox proportional hazards model was used to calculate the hazard ratios (HRs) and 95% confidence intervals (CIs) to explore the association between MetS and its components and CRC risk after adjustments for confounding variables. Results: In total, 128 incident CRC cases were identified during the follow‐up period. An increased CRC risk was found among participants with MetS (HR, 1.63; 95% CI, 1.08‐2.44). Additionally, elevated blood pressure (HR, 1.50; 95% CI, 1.05‐2.15) and a high fasting glucose level (HR, 1.80; 95% CI, 1.23‐2.63) were associated with an elevated risk of CRC. Notably, an increased risk was identified among participants with abdominal obesity coexisting with another component of MetS. Conclusions: These results suggest that MetS is a risk factor for CRC. Greater emphasis should be placed on the importance of CRC screening among individuals with abdominal obesity coexisting with another component of MetS. Lay Summary: Colorectal cancer (CRC) ranks as the third most common cancer type in terms of incidence. Metabolic syndrome (MetS) has been identified as a contributor to cancer development. However, the association between MetS and CRC remains controversial because of a lack of consistent findings in previous studies. In this study, the National Cholesterol Education Program's Adult Treatment Panel III guidelines are used for the diagnosis of MetS. MetS is found to be a predictor of CRC. Additionally, the importance of CRC screening among individuals with 2 components of MetS should be emphasized. Abstract : Metabolic syndrome (MetS) is a risk factor for incident colorectal cancer (CRC), especially among men with abdominal obesity coexisting with another component of MetS who have not developed MetS. These findings emphasize the importance of screening programs designed to detect CRC at an early stage in individuals with abdominal obesity coexisting with another component of MetS.